The Implementation of Religious Activities Development Program Based on Virtualization of Zoom Meetings in Madrasah Ibtidaiyah - Subhan Marpaung; Wahyuddin Nur Nasution; Yusnaili Budianti (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe the implementation of a religious activity development program based on zoom meeting virtualization at MIN 8 Asahan. The focus of the discussion includes the study of teaching methods, materials (learning content), as well as supporting and inhibiting factors in developing religious activities through zoom meetings. Data collection techniques using documentation, interviews, and observations. The data analysis technique uses data reduction, data display, and conclusion drawing. The results of the first study show that the teacher's method is based on aspects of daily, weekly, and monthly activities, based on aspects of the semester and annual activities using the synergetic teaching method. The teacher's material is carried out through evaluation. The evaluation uses an evaluation assessment through oral, written, and deed tests. The supporting factor is the existence of a collaboration between the district ministry of religion and the local education office and the support from school principals, teachers, learning communities, and Madrasah committees. Meanwhile, the inhibiting factor is the lack of available time and volume of distribution of hours for the implementation of activities, meanwhile, the intensity and number of enthusiasts in one activity item takes up to 5 hours, and internet services sometimes experience network disturbances. The lack of optimization of the provision of facilities and infrastructure coupled with the quality of the distribution of developments whose coverage is inadequate, such as fast internet service facilities and development activities outside of school hours is not sufficient.